Mineral-and-energy clusters of the Russian Аrctic and prospects for expanding the outer boundary of its continental shelf - Alexander A. Kremenetsky; Igor G. Spiridonov; Alexey G. Pilitsyn; Ludmila I. Veremeeva (Руды и металлы)
The project of organizing mineral-and-energy clusters with spatial conjugation of deposits of solid minerals (SM) and hydrocarbons (HC) localized on the continental margin and shelf of the Arctic zone of the Russian Federation is substantiated. Four clusters of the kind are characterized, i.e.: Murmansk-Barents, Yamal-Norilsk, Lena-Laptev Sea and Northeast-Chukotka, with the corresponding characteristics of the SM and HC resource bases, as well as substantiation of the bedrock gold and porphyry copper prospective areas in the Northeast-Chukotka cluster. An example of prediction and localization of the HC accumulations in the deep-water part of the Arctic Basin outside the 200-mile zone of the Russian shelf is considered. Geological and morphostructural evidence of the epicontinental nature of the bottom of the Amerasian and Eurasian basins is presented as a criterion for substantiating Russia's right to expand the outer boundary of the continental shelf.